7SK Acts as an Anti-tumor Factor in Tongue Squamous Cell Carcinoma - Zhang, Bowen; Min, Sainan; Guo, Qi; Huang, Yan; Guo, Yuzhu; Liang, Xiaolin; Wu, Li-ling; Yu, Guang-yan; Wang, Xiangting (Frontiers in Genetics, 2021)
Climbing evidences have shown the mechanistic insights about non-coding RNA 7SK in controlling the transcription. However, the biological function and mechanism of 7SK in cancer are largely unclear. Here, we showed that 7SK was downregulated in human tongue squamous carcinoma (TSCC) and acted as a TSCC suppressor through multiple cell-based assays including migration assay and xenograft mouse model. The expression level of 7SK was negatively correlated with the size of tumor in the 73 in-house collected TSCC patients. Through combined analysis of 7SK knockdown RNA-seq and published available 7SK ChIRP-seq data, we identified 27 of 7SK regulated genes that were involved in tumor regulation and whose upstream regulatory regions were bound by 7SK. Motif analysis showed that the regulatory sequences of these genes were enriched for transcriptional factors FOXJ3 and THRA, suggesting a potential involvement of FOXJ3 and THRA in 7SK regulated genes. Interestingly, the augmented level of FOXJ3 in TSCC patients and previous report on THRA in other cancer suggested that these two factors may promote TSCC progression. Supportively, we found that 21 out of 27 aforementioned 7SK-associated genes were regulated by FOXJ3 and THRA, and 12 of them were oppositely regulated by 7SK and FOXJ3/THRA. We also found that FOXJ3 and THRA dramatically promoted migration in SCC15 cells. Collectively, we identified 7SK as an anti-tumor factor and suggested a potential involvement of FOXJ3 and THRA in 7SK-mediated TSCC progression.